Análisis del uso de los medios digitales y su impacto en la cultura de la juventud de la ciudad de Babahoyo - Cullishpuma Quimis, Edinson David (2020)
The next research project was carried out with the aim of being able to analyze the use of digital media and its impact on the youth culture of the city of Babahoyo, whose purpose was to find data indicating what digital means are time they spend and the social networks they use the most. During the analysis it was discovered that before the heyday of digital media, several researchers discussed topics about their possible impact, not only on young people and their culture, but also on the rest of society, some of these authors have been mentioned throughout Research. Due to the geographical extent of the city, thirty-five students in the seventh semester of the social communication career were sampled for the application of the direct observation method and the conduct of surveys, where the results indicated that more than half of respondents said that the use of digital media has influenced the culture of young Babasans and that even a degree of acculturation is evident in them; according to their form of expression that can be evident when they engage in a conversation.